(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Loneliness is one of the most serious epidemics of the 21st century. The World Health Organization (WHO) predicts that by 2030 it will be one of the problems with the greatest impact, along with suicidal behavior. The WHO urges health and social entities to look for solutions and provide answers. Loneliness is a complex, diverse and plural phenomenon. It will delve into the types of loneliness, its prevalence, in which groups feel loneliness, the personal and contextual variables that lead a person to feel loneliness and what individual and social responses become a solution to reduce unwanted loneliness.